2020
DOI: 10.1021/acscatal.0c01923
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoranyl Radical Fragmentation Reactions Driven by Photoredox Catalysis

Abstract: Photocatalytic generation of phosphoranyl radicals is fast emerging as an essential method for the generation of diverse and valuable radicals, typically via deoxygenation or desulfurization processes. This Perspective is a comprehensive evaluation of all studies using phosphoranyl radicals as tunable mediators in photoredox catalysis, highlighting how two distinct methods for phosphoranyl radical formation (radical addition and nucleophilic addition) can be used to generate versatile radical intermediates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 109 publications
2
86
0
Order By: Relevance
“…Intermediate II could then undergo a β-scission fragmentation, giving rise to the desired heteroarene phosphonate and the ethyl radical which evolved to ethane by hydrogen-atom transfer. 25 , 26 , 64 − 69…”
Section: Results and Discussionmentioning
confidence: 99%
“…Intermediate II could then undergo a β-scission fragmentation, giving rise to the desired heteroarene phosphonate and the ethyl radical which evolved to ethane by hydrogen-atom transfer. 25 , 26 , 64 − 69…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, compound 3b reacted with difluoroenolate to form the difluoroalkylated diarylmethane 5 in 83% yield via a Cu(OAc) 2 -catalyzed hydrodifluoroalkylation reaction [ 52 ]. Two other examples were the use of photoredox catalysis to generate acyl anions in situ from aromatic carboxylic acids via a triphenylphosphine-mediated deoxygenation process, followed by reaction with sulfonylated diarylmethane 3b to obtain diarylmethane ketone derivatives 6 and 7 [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37] We employed a direct C-O bond activation strategy via electrochemical generation of the key intermediate of the Mitsunobu reaction. 38,39 Control experiments revealed that the coupling reaction did not proceed in the absence of an electric current, nickel catalyst, ligand, or PPh 3 . Currents ranging from 2 to 4 mA were found to be equally effective (1.1-2.3 mA/cm 2 of graphite).…”
Section: Scheme 6 Proposed Mechanism For the Nickel-catalyzed Crosscoupling Of Aryl Halides With Benzylic Trifluoroboratesmentioning
confidence: 99%